Perioperative nursing care for cochlear implantation in children with congenital ear malformations: A case study - Febryandy, Valentino; Fadly, A. Rizal (Palembang MediRose Publisher, 2025)
Background: Cochlear implantation in children with congenital ear malformations presents unique perioperative challenges due to anatomical variations. Comprehensive perioperative care is essential for optimal outcomes, yet literature on nursing management for these complex cases remains limited. Objective: To document the perioperative nursing approach for cochlear implantation in a pediatric patient with congenital ear malformation and establish evidence-based protocols for similar cases. Case: A 9-year-old child diagnosed with bilateral profound sensorineural hearing loss with Mondini malformation (incomplete partition) underwent left cochlear implantation. The patient had previously undergone right cochlear implantation two years prior with successful outcomes. Perioperative management included comprehensive preoperative assessment with special attention to craniofacial anomalies, intraoperative monitoring for cerebrospinal fluid leakage and facial nerve function, and postoperative care focusing on pain management, infection prevention, and family education. Despite anatomical challenges, the procedure was successfully completed with 10 of 12 electrodes functioning properly, and the patient was discharged on postoperative day two without complications. Conclusion: Successful cochlear implantation in children with congenital ear malformations requires a multidisciplinary approach with specialized perioperative nursing care. This case demonstrates that with proper preoperative planning, intraoperative vigilance, and comprehensive postoperative management, good functional outcomes can be achieved despite complex anatomical challenges. Standardized protocols for perioperative care in these cases can significantly improve patient safety and surgical outcomes.